Biofilm assessment of vibrio parahaemolyticus from seafood using random amplified polymorphism DNA-PCR - Nillian, Elexson; Rukayadi, Yaya; Mahyudin, Nor Ainy; Kantilal, Haresh Kumar; Anyi, Ubong; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
Pathogenic Vibrio parahaemolyticus is one of the leading causes of bacterial gastroenteritis in many countries. Among the strains examined, 36 RAPD-types were found when amplified with primers OPA8 and OPA10. The analysis shows the majority of V. parahaemolyticus isolates originated from seafood were branched into four major clusters at 18.2%, 20.7% 34% and 3.4% similarity levels. This suggests that there is potential for a single strain to be distributed widely within a population and there also potential for multiple contaminating strains of different clonal lineages to be present within the same population. Optimum temperature (37°C) was the highest and stable formation of biofilm. The total percentage of biofilm formation at 37°C was 33.33% for each of weak, moderate and strong biofilm producers. Room temperature produces 61.1% of weak biofilm producer, while 13. 89% for moderate biofilm producers and produce 25% of strong biofilm. While a total of 91.67% weak biofilm producers at 4°C and 8:33% for room temperature and no growth of strong biofilm. Upon analysis, strong biofilm was tracked from the largest group at 37°C and room temperature which produce 27.27% of strong biofilm producer respectively. Interestingly, they are derived from cockles.